New research on parenting programs for low-income fathers - Pearson, Jessica; Fagan, Jay (New York, NY : Routledge, 2021)
"This book explores fatherhood programs, funded by the Fatherhood Research and Practice Network (FRPN), which advance knowledge and practice in the fathering field. New Research on Parenting Programs for Low-Income Fathers synthesizes state-of-the-art findings and provides summaries of key implications for evidence-based practice. Focusing on helping low-income fathers, this volume includes research on how to engage mothers to support father-child contact and to successfully employ social media and online technology for practice. It offers findings on how to increase paternal engagement and parenting skills and to include fathers in policies and programs for children and families. Chapters also discuss future directions for research that encourages effective fatherhood practice. This book is an excellent resource for therapists, social workers, fatherhood educators, fatherhood practitioners, and policy makers on how to inspire positive coparenting and healthy partner relationships"--
The effectiveness of responsible fatherhood programs targeting low-income and nonresident fathers: a qualitative meta-synthesis -- Does curriculum matter? A randomized control study of the "developing all dads for manhood and parenting program (DAD MAP)" curriculum -- Factors associated with fatherhood program effectiveness: a randomized controlled trial of TYRO dads -- Engaging fathers in perinatal home visiting: early lessons from a randomized controlled study of dads matter HV -- Evaluation of Key to Kāne, a text-messaging intervention for fathers in Hawaii -- Challenges and opportunities for engaging unmarried parents in court-ordered, online parenting programs -- A mixed methods study of a mother-only program to enhance coparenting relationships -- Fatherhood and coparenting: a study of engaging mothers in paternal involvement interventions -- Engaging mothers in coparenting services with the nonresidential fathers of their children via fatherhood programs: insights into barriers and solutions -- "You gotta make them feel": a study of evidence-informed strategies for addressing domestic violence in fatherhood programs -- Journey of a policy change to include fathers in homeless shelters -- Information classification: general -- estimating the monetary value of fatherhood programs -- Developing father inclusion policy at the state level: a qualitative assessment of enablers and barriers -- What have we learned and where do we go from here?
OCLC-licensed vendor bibliographic record.
Keywords: Low-income fathers; Fatherhood -- Study and teaching; Fathers -- Education; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family; SOCIAL SCIENCE / Social Work